Risk Factors of Microscopically Tumor-Free Surgical Margins for Recurrence and Survival of Oral Squamous Cell Carcinoma Patients - Pei, Meiling; Han, Dawool; Kim, Ki-Yeol; Kim, Dong Wook; Nam, Woong; Kim, Hyung Jun; Cho, Eunae Sandra; Kim, Hyun Sil; Cha, In-Ho; Zhang, Xianglan (Frontiers in Oncology, 2022)
Objectives The concept of adequate surgical margins remains controversial in oral squamous cell carcinoma (OSCC) surgery. This study aimed to identify surgical margin-related indicators that might impact recurrence and survival of OSCC patients. Materials and Methods Histopathological examination was performed using hematoxylin-eosin-stained surgical margin tissue sections in 235 OSCC patients. Axin2 and Snail expression at the surgical margin was detected by immunohistochemistry. The impact of the Axin2-Snail cascade on tumorigenesis of the immortalized human oral keratinocyte (IHOK) line was investigated in vivo. Results The width and dysplasia of surgical margins were not significantly associated with the outcome of OSCC patients. In a multivariate analysis using variable clinicopathologic factors and with Axin2 and Snail expression as cofactors, higher age (hazard ratio [HR]:1.050; P=0.047), Axin2 (HR:6.883; P=0.014), and Snail abundance (HR:5.663; P=0.009) had independent impacts on worsened overall survival. Similarly, lesion site in retromolar trigone (HR:4.077; P=0.010), upper (HR:4.332; P=0.005) and lower gingiva (HR:3.545; P=0.012), presence of extranodal extension (HR:9.967; P<0.001), perineural invasion (HR:3.627; P=0.024), and Snail abundance (HR:3.587; P<0.001) had independent impacts on worsened recurrence-free survival. Furthermore, Axin2 knockdown induced decreased Snail expression and attenuated tumorigenesis in the IHOK line. Conclusion Histopathological examination of surgical margins may not be reliable to predict OSCC patient outcome. Molecular analysis may provide a more accurate risk assessment of surgical margins in OSCC. In particular, Axin2 and Snail are potential predictive biomarkers for the risk assessment of surgical margins in OSCC.